2015
DOI: 10.1088/0004-637x/812/1/81
|View full text |Cite
|
Sign up to set email alerts
|

Arecibo Pulsar Survey Using Alfa. Iv. Mock Spectrometer Data Analysis, Survey Sensitivity, and the Discovery of 40 Pulsars

Abstract: The on-going Arecibo Pulsar-ALFA (PALFA) survey began in 2004 and is searching for radio pulsars in the Galactic plane at 1.4 GHz. Here we present a comprehensive description of one of its main data reduction pipelines that is based on the PRESTO software and includes new interference-excision algorithms and candidate selection heuristics. This pipeline has been used to discover 40 pulsars, bringing the survey's discovery total to 144 pulsars. Of the new discoveries, eight are millisecond pulsars (MSPs; P 10 <… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
131
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 96 publications
(135 citation statements)
references
References 58 publications
4
131
0
Order By: Relevance
“…Additionally, the bursts from FRB 121102 show a wide range of spectral shapes that appear to be predominantly intrinsic to the source and which vary on timescales of minutes or shorter. While there may be multiple physical origins for the population of fast radio bursts, the repeat bursts with high dispersion measure and variable spectra specifically seen from FRB 121102 support models that propose an origin in a young, highly magnetised, extragalactic neutron star 11,12 .2 FRB 121102 was discovered 4 in the PALFA survey, a deep search of the Galactic plane at 1.4 GHz for radio pulsars and fast radio bursts (FRBs) using the 305-m William E. Gordon Telescope at the Arecibo Observatory and the 7-beam Arecibo L-band Feed Array (ALFA) 13,14 . The observed dispersion measure (DM) of the burst is roughly three times the maximum value expected along this line of sight in the NE2001 model 15 of Galactic electron density, i.e.…”
mentioning
confidence: 70%
See 3 more Smart Citations
“…Additionally, the bursts from FRB 121102 show a wide range of spectral shapes that appear to be predominantly intrinsic to the source and which vary on timescales of minutes or shorter. While there may be multiple physical origins for the population of fast radio bursts, the repeat bursts with high dispersion measure and variable spectra specifically seen from FRB 121102 support models that propose an origin in a young, highly magnetised, extragalactic neutron star 11,12 .2 FRB 121102 was discovered 4 in the PALFA survey, a deep search of the Galactic plane at 1.4 GHz for radio pulsars and fast radio bursts (FRBs) using the 305-m William E. Gordon Telescope at the Arecibo Observatory and the 7-beam Arecibo L-band Feed Array (ALFA) 13,14 . The observed dispersion measure (DM) of the burst is roughly three times the maximum value expected along this line of sight in the NE2001 model 15 of Galactic electron density, i.e.…”
mentioning
confidence: 70%
“…Here we provide a brief description of the Arecibo Mock spectrometer data and search pipeline 14 used for our follow-up observations of FRB 121102. The 1.4-GHz data were recorded with the Mock spectrometers, which cover the full ALFA receiver bandwidth in two subbands.…”
Section: Observations and Search Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Acceleration searches are now widely used in blind surveys (e.g. Lazarus et al 2015), because computing improvements make them feasible as demonstrated by their successes in discovering new DNS systems.…”
Section: Selection Effectsmentioning
confidence: 99%